Percy Bysshe Shelley: The Neglected Genius - Bakić-Mirić, Nataša M.; Lončar-Vujnović, Mirjana N. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Percy Bysshe Shelley (1792–1822) is considered one of the most prolific poets and, at the same time, the most tragic icon of the Romantic Movement in England. His life and poetry certainly support such argument because Shelley’s joy, his love of mankind, intense feelings, imagination, love, freedom, and a profound belief in the perfection of man are unique among all Romantics. This paper gives an outlook of his life, times, critical reception, and his most famous works, which are recognized as leading expressions of his incredible, and, oftentimes, neglected poetic genius.
Keywords: freedom; imagination; love; poetry; Percy Bysshe Shelley